2019
DOI: 10.3390/agriculture9050101
|View full text |Cite
|
Sign up to set email alerts
|

Is a Change of Protein Composition after Late Application of Nitrogen Sufficient to Improve the Baking Quality of Winter Wheat?

Abstract: Concentration and composition of storage proteins affect the baking quality of wheat. Although both are influenced by late nitrogen fertilization, it is not clear whether compositional changes are sufficient to improve the baking quality, and whether such effects are cultivar specific. In a pot experiment, two winter wheat cultivars belonging to different quality classes were supplied with two levels of late N fertilizer. Protein subunits were analysed by SDS-PAGE (Sodium Dodecyl Sulfate Polyacrylamide Gel Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…In relation to N increase (Figure 1), the AG mean generally decreased by 1.1%, but the N effect on cultivars was not consistent, so, in Bologna, Isengrain and San Pastore, the AG proportion decreased by 15.3%, 11.4% and 10.9%, while in Bezostaje-1, Ingenio and Solehio, it increased by 7.2%, 8.4% and 7.5%, respectively. Some authors [12,17,28] noted that AG remained nearly unaffected under the higher N level, while Rekowski et al [29] reported that late N supply significantly increased AG by 8-9%.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to N increase (Figure 1), the AG mean generally decreased by 1.1%, but the N effect on cultivars was not consistent, so, in Bologna, Isengrain and San Pastore, the AG proportion decreased by 15.3%, 11.4% and 10.9%, while in Bezostaje-1, Ingenio and Solehio, it increased by 7.2%, 8.4% and 7.5%, respectively. Some authors [12,17,28] noted that AG remained nearly unaffected under the higher N level, while Rekowski et al [29] reported that late N supply significantly increased AG by 8-9%.…”
Section: Resultsmentioning
confidence: 99%
“…Xue et al [13] claimed that late N fertilizations resulted in a greater accumulation of gluten proteins in some cvs, and in particular of x-type glutenins (HMW-gs Bx7), but the ratios between gliadins and glutenins remained unchanged, thus no improvement in the baking properties of the flour was verified [11]. Rekowski et al [14] observed that late N fertilization increased GPC in both ordinary bread-making and high protein cvs, while significant changes in gluten fractions were only observed as a consequent of a N fertilization strategy for the higher protein cv. The latter study found an increase in the storage protein fractions with a low-to-medium sulfur content, HMW-gs and ω-gliadins, while a slight decrease was observed for LMW-gs, with a consequent reduction in the gs/glia ratio.…”
Section: Effect Of Late-season N Fertilizationmentioning
confidence: 99%
“…The contribution of post-anthesis N uptake, in comparison with the pre-anthesis stored N, which is subsequently translocated to the spikes during late leaf senescence [10], can vary from 5-40% of the final total grain N [11]. The clear effect of a late N fertilization on the increase in the amount of grain protein quantity has been tested and verified in several works [5,6,12,13], while its influence on the change in the gluten protein composition and dough properties seems to be less significant, although opposing opinions are reported in the literature [7,14,15]. Martre et al [7] and Triboi et al [15] claimed that variations in the gluten protein composition are not influenced by the timing or rate of fertilization, and that increases in all the gluten protein fractions can be observed for a higher N supply.…”
Section: Introductionmentioning
confidence: 99%
“…Especially HMW glutenins and ω-gliadins have been suggested to be responsible for the majority of variation in baking quality (Shewry et al, 2001). While the qualitative protein composition seems to be genetically determined, quantity of protein composition especially ω-gliadins and HMW glutenins can be altered by environmental factors such as N supply (Daniel and Triboi, 2000;Altenbach et al, 2003;Rekowski et al, 2019). This is feasible because these subunits have relatively low sulfur contents (Shewry et al, 2002), therefore additional N can be directly used for their synthesis without any S limitation in contrast to S-rich subunits like γ-gliadins (Daniel and Triboi, 2000;Zö rb et al, 2010;Hurkman et al, 2013).…”
Section: Protein Composition Is Influenced By Different N Formsmentioning
confidence: 99%
“…Achieving a good balance between N released from fertilizers and plant N requirement is a major goal in cereal production, since grain protein concentration and composition are primarily influenced by the availability of N during plant development (Guardia et al, 2018). Even though a positive correlation between N availability, protein concentration, and the baking quality has been well documented (Ayoub et al, 1994;Lloveras et al, 2001), there is increasing evidence that optimum baking quality is significantly influenced by protein composition (Wieser and Seilmeier, 1998;Triboï et al, 2003;Rekowski et al, 2019) as well as the distribution of different grain protein subunits and their ratio (Daniel and Triboï, 2002;Veraverbeke and Delcour, 2002).…”
Section: Introductionmentioning
confidence: 99%